ANALISIS BUKU PELAJARAN FISIKA SMA KELAS XI YANG DIGUNAKAN DI SALATIGA (UPEJ Unnes Physics Education Journal, 2013)
This study aimed to analyze the quality of textbooks covering the subject feasibility factors, linguistic factors, presentation factors, and graphic factors on textbooks for eleventh grade of senior high school in Salatiga. The population of this study is the physics textbooks. The samples are Book A and Book B. Book A written by Marthen Kanginan and published by Erlangga. Book B written by Supiyanto and published by Phibeta. This study used descriptive qualitative to analyze the data. The results of the analyze of subject feasibility factors, linguistic factors, presentation factors, and graphic factors of Book A 96,53 %, 100%, 76,39%, 91,67%, then Book B get the scores 62,78%, 75,76%, 89,77%, 95,83%. Based on the result of analysis above, it could be concluded that Book A belonging to the criteria of â€œvery goodâ€, and Book B belonging to the criteria of â€œgoodâ€.